Retropharyngeal foreign body in a Down Syndrome girl (Bangladesh Journal of Medical Science, 2019)
Pharyngeal foreign bodies are quite common. The diagnosis is usually clinical. The risk of complications including retropharyngeal abscess and mediastinitis are very low depending on the nature of foreign body and the duration taken for intervention. We share a challenging case of retropharyngeal abscess secondary to embedded foreign body in a Down syndrome patient, who presented with the sole presentation of torticollis. Surgical intervention with difficulties was performed with favourable outcome.Bangladesh Journal of Medical Science Vol.18(3) 2019 p.641-645